Growth Performance, Haematology And Blood Serum Chemistry Of Weaner Rabbits Fed Parboiled- Sundried False Yam (Icacina Trichantha) Meal At Varying Replacement Level For Maize. (Global Journal of Science Frontier Research, 2018)
A seven-week feeding trial was conducted at the Rabbitary Unit of the Teaching and Research Farm, Ambrose Alli University, Ekpoma to evaluate the growth performance, hematology and serum biochemistry of 15 unsexed weaner rabbits fed varying levels of Parboiled sundried false yam (Icacina tricantha) meal. Five treatments were formulated with diet one containing 100% maize as control, while in diet two, three, four and five parboiled sundried false yam meal replaced the percentage proportion of maize in diet one at 25, 50, 75 and 100% inclusion level respectively. Each rabbit was randomly assigned to the five treatment diets in a complete randomized designed (CRD) each treatment group contained three replicates with one rabbits each. Performance characteristics revealed that final live weight and weekly feed intake were significantly (P
Keywords: broiler chicken; growth performance haematology; serum; parboiled-sundried false yam